Spray Printing of Porous Substrates from Nanosuspensions - Panduro Vela, David; Schlumberger, Carola; Thommes, Matthias; Bück, Andreas (Processes, 2023)
In this work, we present and characterise an experimental setup that allows the generation of porous packings from nanosuspensions. By defined positioning and drying of solid-containing droplets, large-scale porous structures can be generated. Examples of such structures are shown and characterised. Operational challenges are presented, and it is discussed how they can be overcome to allow the maximum degree of freedom in packing generation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: drop-on-demand; drying; porosity; suspension; textural characterization